EFFECTS OF Bryophyllum pinnatum EXTRACTS ON LIVER ENZYME FUNCTION IN MALE WISTAR ALBINO RATS EXPOSED TO PREMIUM MOTOR SPIRIT (PMS) - Edoga, Cyril Onyekachi; Olukemi , Sowunmi Kehinde; Okoh, Emmanuel Chidera (Global Journal of Medical and Health Science, 2025)
Exposure to Premium Motor Spirit (PMS) can cause hepatotoxicity, which is typified by changes in liver enzyme levels. In this work, male wistar albino rats subjected to PMS were used to examine the hepatoprotective effects of Bryophyllum pinnatum extracts on liver enzyme activity. Five (5) groups of rats were created: low-dose extract, medium-dose extract, high-dose extract, blank control, and negative control. Every group—aside from the blank control group—was subjected to PMS inhalation. Following a 28-day experiment, liver enzyme activity (ALT, AST, ALP, and GGT) were measured. Exposure to PMS markedly elevated liver enzyme activity, suggesting hepatotoxicity. Hepatoprotection was suggested by the considerable reduction in liver enzyme activity following treatment with Bryophyllum pinnatum extract. Compared with the blank control (30.48 ± 0.01) in week 2, the results indicated a dosage-dependent decrease in AST enzyme activity, with the highest dose (29.85 ± 0.12) showing the most significant reduction (p>0.05), followed by the medium-dose at (31.74 ± 0.32). At week 4, the outcomes showed the same trend. These results suggest that Bryophyllum pinnatum extracts can be used as a medicinal agent because they can lessen PMS-induced hepatotoxicity